Impacts of domestication on angling vulnerability of common carp, Cyprinus carpio: the role of learning, foraging behaviour and food preferences. (5th November 2012) - Klefoth, T.; Pieterek, T.; Arlinghaus, R.
Abstract Domestication in fish selection increases vulnerability to angling. Two common garden‐reared genotypes of common carp, Cyprinus carpio L., differing in degree of domestication (highly domesticated mirror carp and less domesticated scaled carp) were exposed to fishing in two environments (i.e. ponds and laboratory tanks) to quantify vulnerability to angling. Foraging behaviour and food preferences were quantified to explain variation in angling vulnerability in a mechanistic manner. Domesticated mirror carp were more vulnerable to angling gear than scaled carp in both environments, which was related to greater food intake and bolder‐foraging behaviour. Independent of genotype, catchability decreased and time until first capture increased over fishing time, indicating learned hook avoidance. No differences were observed in food preferences among genotypes, rendering bait‐selective feeding an unlikely explanation for differential vulnerability to angling. It was concluded that vulnerability to angling has a genetic basis in carp and that boldness plays a paramount role in explaining why more domesticated genotypes are more easily captured by angling.